Prevalence of polycystic ovarian syndrome among adolescent girls: a prospective study - Singh, Archana; Vijaya, K.; Sai Laxmi, Kaparati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: PCOS is a complex endocrine disorder which is most common in women of reproductive age. PCOS may first present in adolescence, but the incidence of PCOS in adolescence is not known, as diagnostic criteria for PCOS in the adolescent age-group is still not defined, PCOS symptoms tend to overlap with normal pubertal changes making the diagnosis even more challenging. The objective is to study prevalence and symptomatology of polycystic ovary syndrome (PCOS) in adolescent girls. Methods: Prospective study between November 2017 and March 2018. 117 adolescent girls aged 15 to19 years attending OPD with oligomenorrhea and/or hirsutism were advised for biochemical, hormonal, and ultrasonographic evaluation for diagnosis of PCOS on the basis of Rotterdam’s criteria at the Department of Obstetrics and Gynaecology, Government Maternity Hospital, Osmania Medical College, Hyderabad. Results: Prevalence of PCOS in the study was 11.96% in the study group. Conclusions: PCOS is increasingly encountered during adolescence, although the overall prevalence is low and evaluation of PCOS in adolescents is challenging. At this age, life style modification is imperative to prevent long-term metabolic and reproductive complications.